Innovation In Anemia Prevention Among Adolescents, Women Ofchildbearing Age, Pregnant Women, Postpartum Women, and Toddlers With Jupalof - Ade Mona Julia Putri; Putri Azzahroh; Ritha Widyaputri (Rajaki of Tulip Medika Publisher, 2026)
Background: Anemia is associated with cognitive and motor development disorders in infants and children; in adolescents and WUS, it reduces quality of life, educational effectiveness, and reproductive health. Therefore, prevention methods that can improve iron levels offer benefits to communities and families in both the short and long term. JUPALOF, a mixture of Ambon banana juice and low-fat milk, is a functional food designed to prevent anemia. the JUPALOF formulation must balance the ratio of ascorbic acid (vitamin C) to calcium content by adding additional fortification and selecting low-fat milk and Clinical studies show that iron absorption can be significantly improved with vitamin C. Purpose : This community service was carried out with the aim of addressing the problem of anemia found in the TPMB Enok Siti Roiyatul area. Method: The method used in this community service involve lectures, discussions, and demonstrations. This study targets pregnant women with anemia in the TPMB Enok Siti Roiyatul area. Result: From the results of community service activities, mothers understand that JUPALOF is a banana drink with low-fat milk that can prevent anemia if consumed regularly and accompanied by a healthy diet and adherence to iron supplements as recommended by health workers. Conclusion: Based on an evaluation conducted after providing education on banana juice with low-fat milk, pregnant women gained increased knowledge about anemia, its impact on health, and the importance of balanced nutrition. The JUPALOF innovation, as a nutritious beverage alternative, was considered easy to make, easy to obtain, and acceptable as a beverage that can prevent anemia when consumed regularly. Keywords: Anemia; Banana; Nutrition Education; Pregnant Woman